IMPLEMENTASI LINEAR CONGRUENT METHOD PADA GAME JIGSAW PUZZLE TOKOH PEWAYANGAN - Paulus Harsadi; Sri Siswanti; Sanjai Kurniawan (Universitas Katolik Musi Charitas, 2022)
Ethnic diversity and geographical differences make Indonesia rich in various cultures. about wayang, which is already known to many Indonesians, but now Indonesians are increasingly forgetting folklore from within the country and prefer to idolize foreign story characters because most of them are abroad in delivering story content into video games that look interesting. Therefore, so that the public, especially children, are interested in wayang characters, an Android-based jigsaw puzzle game for the Pandawa five puppets was made with an attractive and modern appearance. This study aims to make young children and adults interested in wayang characters, so a